On ant-like Synemosyna Hentz, 1846 spiders from Bolivia, with indirect evidence for polymorphic mimicry complexes (Araneae: Salticidae: Simonellini) - Perger, Robert; Rubio, Gonzalo D.; Haddad, Charles R. (European Journal of Taxonomy, 2021)
Three species of Synemosyna Hentz, 1846 were recorded during a survey in five Bolivian forest ecoregions: S. aurantiaca (Mello-Leitão, 1917), S. myrmeciaeformis (Taczanowski, 1871) and S. nicaraguaensis Cutler, 1993. Synemosyna aurantiaca and S. nicaraguaensis are recorded for Bolivia for the first time and the previously unknown male of S. nicaraguaensis is described and illustrated. The habitus and the genitalia of the female of S. myrmeciaeformis are illustrated for the first time. Synemosyna aurantiaca occurs in semi-deciduous forests south of 18° S and S. myrmeciaeformis in the Bolivian Yungas forest and ecoregions of the Amazon biome north of 16° S. Synemosyna nicaraguaensis is possibly an Andean species that enters into the moist Isthmian forests of Central America. Several potential mimicry complexes with two broad patterns were observed: sex-specific polychromatic mimicry (S. nicaraguaensis), and transformational mimicry involving smaller orange and larger brown to dark-brown forms (S. aurantiaca and S. myrmeciaeformis).